Updating the distribution of Dicrodon guttulatum Duméril & Bibron, 1839 (Reptilia, Teiidae) with a disjunct population in the eastern slope of the Peruvian Andes - García Bravo, Antonio (2022)
We report a disjunct population of Dicrodon guttulatum Duméril & Bibron, 1839 on the eastern slope of the Cordillera Occidental in the inter-Andean Seasonally Dry Forests of the Marañón River, in the Departments of Cajamarca and Piura in northwestern Peru. We include an updated range distribution map using records from museum specimens, the Global Biodiversity Information Facility, and available photographic records on iNaturalist. In addition, we identify widespread cultivation of rice crops as the main threat to D. guttulatum in the inter-Andean Seasonally Dry Forests of the Marañón.